PtAu Nanoparticle as a Catalyst for Ethanol Electrooxidation - Amelia Sabella; Annisa Auliya (Chemistry and Materials, 2023)
In this work, PtAu nanoparticles were successfully synthesized using the electrodeposition technique. The nanoparticles obtained were irregularly spherical in shape and in the size range of 20-200 nm. X-ray diffraction (XRD) confirmed that the formed PtAu nanoparticles were alloys, because they showed a peak of 2θ in the region between Pt and Au metals, namely at 2θ 39.15˚ and 45.53˚. The cyclic voltammetry (CV) test showed that the PtAu catalyst has an ethanol electrooxidation activity of 22.9 mA/cm2, 11 times higher than the Pt catalyst previously synthesized using the same technique and conditions. In addition, at 300–1000 cycles the ethanol electrooxidation performance is fairly constant, indicating that this catalyst is quite stable. Interestingly alloying Pt with Au also increases the poisoning resistance of the catalyst from CO or other intermediate species. Thus, the use of PtAu catalysts can effectively increase catalytic activity, maintain stability of the catalyst, and reduce the possibility of poisoning by intermediate species.